If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(4x+5)-x=4-3x
We simplify the equation to the form, which is simple to understand
6(4x+5)-x=4-3x
Reorder the terms in parentheses
+(+24x+30)-x=4-3x
Remove unnecessary parentheses
+24x+30-x=+4-3x
We move all terms containing x to the left and all other terms to the right.
+24x-1x+3x=+4-30
We simplify left and right side of the equation.
+26x=-26
We divide both sides of the equation by 26 to get x.
x=-1
| 4x+15-6x=17-16x+14x-2 | | 5a+9=9 | | (7p-1)(49p^2+7p+1)= | | 4x+8=2(x-6) | | y+6=1.7(x+4) | | 36+6v=-6(8-8v) | | 6y=9x | | 6y-9x= | | -2x+1=5x-20 | | x^2-3x-11=-6x-1 | | -5y+2=6y+7 | | x=5-2y | | 3k+5=21-5k | | -2x+9=15 | | 42-5x=4x+16 | | 10-7x=65-42 | | 4+2y=12 | | -5(3n+5)=115 | | 5x+10=-2-7x | | 12-5a=-4(2+2a)-2a | | 2.1x-2.16=0.84-5.4x | | -5(5n+5)=115 | | (7p-1)(49p^2+7+1)= | | y-200=7(x-20) | | x+5=216 | | 36+12x=43+25x+15 | | 15q-16=13 | | -(3+n)=-27-5n | | 3+5+7=152192 | | 50440-x(.20)=260000 | | 26-4n= | | 6x+77=14x-11 |